KAJIAN PROSES PERANCANGAN PERLENGKAPAN BANTU DUDUK DI WC BUAT LANJUT USIA - Santoso, Angelia; Judianto, Oskar (CV SWA Anugerah, 2025)
Old age is a period of life that every human being will experience as a final period. In this period, it is closely related to the challenges of physical limitations, such as lack of balance and difficulty walking. This feud certainly had a big impact movement of the elderly in daily life, especially in use Sanitary products similar to using a toilet seat. the toilet seat has as a solution for the elderly's daily movements. but on toilet use sitting, the user must use safety or security measures to avoid the risk of accidents such as falling due to slipping in the bathroom. In this research, a toilet chair product was designed for the elderly so that they do not need to go to the bathroom. The results of this research are a toilet chair product that can adapt to the user when the user is urinating or defecating.